CP-095 Is the emergency pharmacist role accepted by emergency department staff?. (24th February 2014) - Lopez Martin, C; Alvaro, E; Agüera, C; Blanco, ME; Garrido, M; Faus, V
Abstract : Background: Resistance from physicians and nurses is seen as a potential blockage to implementation of an emergency pharmacist programme. Purpose: To examine the perceived value of the emergency pharmacist (EP) role from the perspective of emergency physicians and nursing staff. Materials and methods: Descriptive survey study. A pharmacist carried out clinical tasks in the emergency department for two months. After this time, physicians and nursing staff were surveyed anonymously using a 17-item survey. Five-point scales were used where appropriate (1 = 'strongly agree' and 5 = 'strongly disagree'). Results: We analysed 50 surveys (42% nurses, 58% physicians). 96% of respondents felt that the EP improved quality of care, 68% considered the EP should be an integral part of the team and 91% consulted the EP at least once. Staff highly valued the role of the EP as a staff member and patient educator (90% and 76%, respectively). They found the EP to be useful in consultations regarding: medicines interactions (96%), medicines used in pregnancy (96%), toxicology (96%) and medicines reconciliation (88%). Accessibility to consultations, information regarding drugs, medicines reconciliation and sense of safety were the most valued attributes of the EP. Respondents gave the role of EP a score of 7.6 (SD 1.8) out of 10. Conclusions: An EP is highly valued by staff and it is perceived to improve quality of care. Staff acceptance should not be a barrier to the implementation of EP programmes. No conflict of interest.